Eco-zoning Reserve the Planing of Aquaculture in 08 Coastal Provinces, Mekong Delta, Vietnam - Xuan , Hoan Nguyen; Huy, Ba Le; Minh, Thanh Le (Research Aspects in Biological Science Vol. 1, 2022)
In this study, there are four main factors. It is essential that only elements that create a clear grouping of objects are selected as the basis for zoning. These factors are selected as zoning criteria to compare the types of ecological characteristics of certain types of aquatic products raised in each cultured or future cultured area (including 12 main criteria). The results in 8 coastal provinces of the Mekong River Delta have all 9 aquaculture ecological regions. On the other hand, the study results also set up 8 maps. Detail t For 8 provinces and the whole region is a map of Fertility zoning with the scale of 1/500 000 with careful explanations, showing different quakha1 of colors. This, in fact, has helped to manage and operate the aquaculture environment in line with this valuable ecosystem and coastal resource.